Study on the compression performance of RC columns confined with CTRC based on ICCP technology in chloride environment. (October 2022) - Zhang, Qin; Zheng, Nai-Hao; Gu, Xiang-Lin; Jiang, Yong; Liu, Rong-Hao
Highlights: Compression performance of CTRC-confined columns protected by ICCP in chloride environment is examined. ICCP technology effectively improved the corrosion resistance of CTRC-confined columns. Corrosion model of CTRC-confined columns with ICCP technology is established. Bearing capacity model considering the double protection of CTRC and ICCP technology is proposed. Abstract: In this paper, to study the corrosion resistance and compression performance of RC columns confined by carbon textile-reinforced concrete (CTRC) under impressed current cathodic protection (ICCP) technology in a chloride environment, a total of 30 CTRC-confined square columns were examined through axial compression tests. The effects of the parameters such as different protection potentials of ICCP technology, textile ratios, stirrup ratios, and specimen sizes on the bearing capacity and deformation performance were investigated. The experimental results indicated that the corrosion of the reinforcement in the protected specimens in a chloride environment was significantly reduced under the ICCP technology compared to the control columns. In addition, the maximum reduction in the corrosion level (mass loss degree) of the transverse and longitudinal reinforcement reached 96.43 % and 96.30 %, respectively corresponding to a potential of −0.70 V and −1.00 V. The bearing capacity and deformation performance of the CTRC-confined RC columns were significantly improved by using the ICCP technology. The maximum load and nominal effective deformation of the protected columns were increased by 29.87 % and 62.54 %, respectively, corresponding to the potential of −0.70 V. In addition, the compression performance was also found to have been affected by textile ratios, stirrup ratios, and specimen sizes. Finally, semi-empirical and semi-theoretical analytical models for predicting corrosion level and bearing capacity were established and validated through the experimental data. The proposed models exhibited a good correlation with the experimental data of CTRC-restrained RC columns subjected to axial loads under the protection of ICCP technology.